Developing a Worksite-based Culturally Adapted Smoking Cessation Intervention for Male Hispanic/Latino Construction Workers. (11th May 2018) - Dietz, Noella A.; Asfar, Taghrid; Caban-Martinez, Alberto J.; Ward, Kenneth D.; Santiago, Katerina; Ruano-Herreria, Estefania C.; McClure, Laura A.; Lee, David J.
Abstract : Introduction: Over 2.6 million Hispanic/Latino construction workers (CWs) live in the US; 91% of South Florida CWs are Hispanic/Latino. CWs have higher smoking and lower cessation rates than other workers. Limited access to cessation services, worksite turnover, and lack of interventions tailored to culture/occupation hinder cessation. Partnering with worksite food trucks to deliver unique cessation interventions may improve these efforts. Aims: To explore a novel cessation approach, assess worker/worksite acceptability, and seek input into intervention development. Methods: In 2016, we conducted five semi-structured focus groups with 37 smoking Hispanic/Latino CWs. Constant comparative analysis was used to examine a priori themes regarding smoking behaviours, cessation treatments, intervention delivery, cultural adaptation, and quit interest. Results: CWs reported tremendous job stress. Most smoking occurred during the workday and most CWs did not use nicotine replacement therapy with past quit attempts. Most CWs were open to a worksite face-to-face group cessation intervention before work (many underutilize breaks and feel pressure to keep working). CWs felt it unnecessary to tailor the intervention to Hispanics/Latinos indicating smokers are the same regardless of race/ethnicity. Conclusions: Findings demonstrate the need to consider work environments, job demands/stress, and worker preferences when developing accessible and acceptable cessation interventions.